Pneumatology (The Role of the Holy Spirit) in the Synoptic Gospels: Its Relevance for the Church's Mission Today - Pardede, Harold Walfried (Scriptura Indonesia, 2023)
This research seeks to examine the function of the Holy Spirit in the Synoptic Gospels (Matthew, Mark, and Luke) and its implications for the contemporary mission of the church. In the Synoptic Gospels, the Holy Spirit is shown as a divine being present from the birth of Jesus, through His baptism and ministry, to the commissioning of the disciples. The Holy Spirit is perceived not just as heavenly power but also as a Helper and Teacher who supports the church in proclaiming the Gospel and fulfilling its prophetic mission among contemporary problems like pluralism and secularism. This study employs a qualitative methodology incorporating biblical and systematic theological analysis. This study asserts that an accurate comprehension of the Holy Spirit's role is vital for enhancing spirituality, guiding ministry, and ensuring the sustainability of the church's mission in the modern age. Consequently, the examination of pneumatology through the lens of the Synoptic Gospels offers a robust and relevant basis for contemporary church life and mission.